Um modelo de redes de mapas acoplados para um sistema praga-predador-inseticida - Cereser, Henrique Bevilaqua (2016)
This research is inserted in the Biomathematics Research Group of the Programa de Pós-Graduação em Matemática of the Universidade Federal de Santa Maria-RS. It consists in the study of a discrete model for a prey-predator-insecticide system based on the Coupled Map Lattice as basic tool for its formulation. Due to the serious problems that crop pests represent to agriculture, we aproached the Integrated Pest Management (IPM), which is a pest control system that seeks to preserve and enhance the natural mortality factors of pests by integrated use of control methods selected based on technical, economic, ecological and sociological parameters. The objective of this work is to build a model as simple as possible to study the effects of different pests management strategies. These strategies are divided into different treatments which take into account the number of measurements of pest population, establishing control levels (CL) and different control measures (pesticide and biological control). For comparison and to point where the treatment is more efficient to compute the total density of the pest population without any control measure and when each treatment is applied over a certain period of time. The difference between these values is converted into a decreasing percentage of the population of pests. The same is done to obtain the percentage decrease in the number of treated sites. It was found that the sooner you apply the insecticide in the system, the more effective the treatment. Furthermore, it was observed that the presence of predators (biological control) decreases the amount of treated sites and, in some instances, is less effective in controlling pest.